Effects of teaching internships on preservice teachers’ noticing in secondary mathematics education - Bastian, Anton; König, Johannes; Weyers, Jonas; Siller, Hans-Stefan; Kaiser, Gabriele (Frontiers in Education, 2024)
In this study, we examined the effects of teaching internships and related opportunities to learn, such as conducting lessons or reflecting on teaching practice, on the three facets of teacher noticing, perception, interpretation, and decision-making. Cross-lagged effects of these facets were examined to include reciprocal influences of the facets on each other and to facilitate insights into the development of teacher noticing and how its three facets can predict this development. In detail, this study addressed the research questions of whether and to what extent teacher noticing changes over the course of a teaching internship and how teaching internship process variables influence changes in teacher noticing skills. Based on a sample of 175 preservice teachers from six German universities, we studied their professional noticing using a video-based pre-and posttest approach. The results indicated a significant improvement in all three facets of teacher noticing over the course of the internship with small effect sizes, and interpretation was a key facet in this development, having an autoregressive impact as well as influencing the development of perception and decision-making. Only some opportunities to learn within the teacher internship showed a significant impact on teacher noticing skills. For instance, connecting theory and practice and reflecting on practice seemed to foster teacher noticing skills, while the sole process of teaching had no effects on interpretation or decision-making, and even had a negative effect on perception. Overall, the study demonstrated the potential of teaching internships for the development of preservice teachers' noticing skills and highlighted areas for improvement.